Inflamación de glándulas salivales: revisión bibliográfica - Ospina-M., Ana María; Del Valle-R., Andrés Felipe; Naranjo-R., Rodrigo Felipe (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Salivary glands are symmetrical structures located near the ramus and the body of the mandible. They are the parotid glands (serous saliva), sub maxillary (predominantly serous) and sub lingual (predominantly mucous); besides numerous minor salivary glands exist on the surface of the buccal, yugal, palatine and sub lingual mucosa (300-400 approximately) that produce mucous saliva. The purpose of this literature review, is to present the difeferent infectious processes that affect the glands, the different diagnostic approaches and the treatment guidelines. The infectious disorders of the salivary glands are within the area of the responsibility of the dentistry, and every dentist must be acquainted with these disorders, with the available technologies of diagnosis and must be able to refer those cases that need the care of a specialist.